Knowledge management Practices in Malaysian Higher Learning Institutions: a review on selected case - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah; Yousif, Ahmad (Contemporary Research Center Australia, 2014)
This article underlines the fact that Malaysian Higher Learning Institutions (MHLI) are seriously geared in approaching its academic excellence status, becoming an international education hub attracting students from different parts of the world by offering a comprehensive list of programmes and specialisation. This is due to the fact that knowledge is viewed today as the most important factor in realizing actual growth, creating new values and advantages in a globalized economy. The focus here is on the important of knowledge management (KM) practices within MHLI with the argument that academic institutions should always manage knowledge properly and effectively to allow them to succeed and flourish. However, there is uncertainty about whether the use of KM can be competitive in which it is capable of helping the institution’s approaches and strategies to obtain the quality of education mentioned. This justifies the aim of the present study to review the KM practices in MHLI in order to highlight the functional features of its application.